Brain edema after oocyte retrieval: a case report - Lijuan Fan; Wen Wen; Hanying Zhou (BMC, 2022)
Abstract Background Brain edema is a rare and serious complication of assisted reproductive technology (ART). The increased intracranial pressure and injured brain parenchyma are life-threatening and may even result in death. The pathogenesis may involve increased vascular permeability mediated by vascular endothelial growth factor and other vasoactive substances, including interleukin 6, interleukin 1β, angiotensin II, insulin-like growth factor 1, transforming growth factor β, and the renin-angiotensin system. Case presentation We presented a unique case report of a 29-year-old woman developed sudden irritability, blurred consciousness, and vomiting 8 h after oocyte retrieval. Blood examinations showed hyponatremia and cranial computed tomography showed swelling of the brain parenchyma. After therapeutic use of hypertonic saline and mannitol infusion, the patient's consciousness recovered and her neurological state improved. Conclusions Brain edema is a rare and serious complication of ART. Quick infusion of hypertonic salt solution and mannitol is a key treatment. A good prognosis can be achieved after prompt treatment.